Antimicrobial, antioxidant, and antimutagenic activities of Gladiolus illyricus. - Burcu Basgedik; Aysel Ugu; Nurdan Sarac (Journal of Pharmacy & Pharmacognosy Research, 2014)
Context: In the present study, the ethanolic extracts of the aerial parts and the rhizomes of G. illyricus were obtained. Aims: To determine the antimicrobial, antioxidant, and antimutagenic properties of G. illyricus extracts. Methods: The antimicrobial activity was studied with the disc diffusion method and the antioxidant capacity by inhibition of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and the total antioxidant activity. The antimutagenic activity was investigated by Ames Salmonella/microsome mutagenic test. The bacterial mutant strains Salmonella typhimurium TA98 and TA100 were used to determine antigenotoxic potentials of the extracts. Results: The ethanolic extracts of the aerial parts and the rhizomes showed moderate antimicrobial activity only on Bacillus subtilis. The IC50 value for DPPH radical of the aerial parts and rhizomes were 57.1 ± 1.3 and 48.1 ± 1.1 mg/mL, respectively. The total antioxidant activities of the aerial parts and the rhizomes of G. illyricus at 3.15 mg/mL concentration were 92.3 ± 1.4% and 91.5 ± 2.1%, respectively. These extracts showed antimutagenic effects at 0.5 and 5 mg/plate concentrations. Conclusions: To our knowledge, this is the first study on antimicrobial, antioxidant, and antimutagenic activity of the ethanolic extracts of the aerial parts and the rhizomes from G. illyricus. Our results indicate that the used of these extracts would exert several beneficial effects by virtue of their antioxidant and antimutagenic activities. These activities could be an important topic in the medical and cosmetic fields.